A psicopedagogia na trincheira: contribuições para a valorização social do trabalho precariado dos garis - Dias, Alice Maria André (2019)
The world of work is always changing in the course of time, whether in the social or the enacting aspects. These aspects directly affect the quality of life of the proletarian worker. In this sense, the research developed here tries to bring the perspective of the Garis of the city of João Pessoa in the search to identify the precarious work and to show the role of the psychopedagogue to build in the construction of the professional identity and to establish possible paths for valorization of these workers. Psychopedagogy is an area of knowledge that has as object of study the learning processes of the human being in several spaces, such as: schools, clinics, hospitals and companies. His work is preventive and interventional in all its fields of activity. It can collaborate in a significant way for the improvement of the labor and social reactions of the workers object of this study. The guiding question that guided this research was formulated as follows: How this research can contribute to better know and characterize the modality of work popularly known as garis, but also to indicate possibilities to improve the working conditions of these precarious workers in the city of João Pessoa (PB)? Its general objective is: To characterize the work of the garis within the perspective of precarious work, as well as to identify the contributions of Psychopedagogy to the improvement of their working conditions and the construction of their professional identity, as well as to discuss the world of work in the contemporaneity emphasized alienated work; Conceptualizing the precarious within a sociological perspective; Analyze the perspectives of the garis and how the formation of the precarious in this class occurs; To conceptualize Psychopedagogy, starting from its historical framework; To suggest actions of Psychopedagogy for workers of the precarious class to establish ways to build a professional identity and social valorization. From the methodological point of view, this is a qualitative, documentary and exploratory research using observations and labor legislation to be based on the construction of the interview for the collection of necessary data. With this, it is expected that this work may bring relevant information to improve the relationships of garis' work.